EXPERT STUDIES OF THE QUALITY OF PICKLED BIOFORTIFIED TOMATOES IN TERMS OF SAFETY INDICATORS - YUDICHEVA, Оlha; ALAVERDIAN, Liudmyla; KHLIEBNIKOVA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
An expert study of the quality of pickled biofortified tomatoes was conducted according to safety indicators (content of toxic elements - lead, cadmium, arsenic, mercury; nitrate content; content of pesticide residues; content of aflatoxin B1 and patulin). Tomatoes for processing are grown using innovative technologies of agronomic biofortification. Organic fertilizer “Riverm” was used, which provides a natural increase in the content of vitamins and minerals in vegetables. The results of the study revealed that the content of toxic elements in the test sample does not exceed acceptable levels. Nitrates are 2.5 times less than allowed for this type of food. The content of pesticides in the prototypes of pickled tomatoes is less than the sensitivity limit of the method used for the study. In the studied samples of pickled biofortified tomatoes the content of mycotoxins does not exceed the permissible levels. Based on the results of expert research, a conclusion was made - the product samples meet the requirements of regulatory documents and are safe for consumers.
Keywords: pickled tomatoes; agronomic biofortification; expert research; “Riverm”; toxic metals; mycotoxins; pesticides